Finger Hold Relaxation Combined with Ginger Aromatherapy for Emesis Gravidarum - Palupi, Retno; Febrina, Lydia; Sari, Wenny Indah Purnama Eka (Journal of Midwifery and Nursing, 2024)
Pregnancy is a period from conception to childbirth, involving complex physiological and psychological adjustments due to significant hormonal and physical changes. One of the main symptoms in the early stages of pregnancy is nausea and vomiting, which hormonal changes, emotions, or anxiety can cause. This study aims to determine the effect of finger hold relaxation combined with ginger (Zingiber Officinale) aromatherapy on emesis gravidarum in first-trimester pregnant women in the work area of Puskesmas Embong Ijuk, 2024. The research method used is a pre-experiment with a one-group pre-test-post-test approach without control. The research sample consists of 24 first-trimester pregnant women with emesis gravidarum, selected using purposive sampling technique. The instrument used is the PUQE-24 questionnaire. Data analysis was performed using the Wilcoxon test. The analysis results show a significant difference between pre-test and post-test values (p-value = 0.000), indicating the influence of finger hold relaxation combined with ginger aromatherapy on emesis gravidarum in first-trimester pregnant women. Finger hold relaxation effectively reduces stress that can trigger nausea, while ginger aromatherapy acts directly on the symptoms of nausea through chemical pathways. This combined approach provides holistic treatment that considers not only physical symptoms but also the mental well-being of pregnant women. It is hoped that first-trimester pregnant women can apply finger hold relaxation combined with ginger aromatherapy as an alternative non-pharmacological therapy to treat emesis gravidarum.